Communication in open disclosure conversations about adverse events in hospitals. (March 2015) - Watson, Bernadette M.; Angus, Daniel; Gore, Lyndsey; Farmer, Jillann
Abstract: We analyzed eight interactions between clinicians and simulated patients or family members discussing adverse events in patient care. We targeted the interactants' accommodative communication strategies when they discussed the consequent patient harm. In Study 1, 80 psychology students rated eight open disclosure video recordings for the presence of CAT strategies. In the recordings categorized as effective, clinicians demonstrated accommodative emotional expression and interactants engaged in more accommodative interpretability and interpersonal control strategies than in ineffective recordings. In Study 2, the same recordings were analyzed using Discursis (a textual analysis software program). Discursis uses new technology to visualize and identify speaker approximation. Approximation patterns correlated with findings from Study 1. Results provide insights into which CAT strategies assist managing open disclosure. Highlights: Communication Accommodation Theory explains effective open disclosure interactions. The studies investigate accommodative communication strategies in open disclosure. Discursis is a useful new computer program that can measure approximation.